Nutraceutical profile of goji (Lycium barbarum L.) berries in relation to environmental conditions and harvesting period. (October 2022) - Poggioni, Letizia; Romi, Marco; Guarnieri, Massimo; Cai, Giampiero; Cantini, Claudio
Abstract: Goji ( Lycium barbarum L.) berries are well known for their biological activities and health-promoting antioxidant properties. Environmental and climatic factors can greatly affect accumulation of secondary metabolites, carotenoids and other antioxidants in plants. We determined the content and composition of main functional constituents of goji berries produced in central Italy in relation to the time of harvesting during two ripening seasons by analyzing the main environmental variables involved. The highest flavonoids content (0, 19 ± 0, 006 mg QE/g) and antioxidant power (0, 03 ± 0, 001 mmol Fe 2+ eq/g) were found at the beginning of the fruiting season. In September, berries show the highest total polyphenols (3, 22 ± 0, 09 mg GAE/g) and zeaxanthin contents (339, 79 ± 14, 12 μg/g). Our study focused on some important aspects related to the production of goji fruits with high nutraceutical characteristics in a non-experimental cultivation. Our results could provide reliable information on Goji performance in the European climate to be used for the exploitation of the species suggesting the best harvesting timing in terms of antioxidant power and nutraceutical features of berries. This information could be particularly useful for farmers eager to improve the quality of their products.